Det stadsnära jordbrukets förutsättningar – Fallet Malmö och Stadsbruk - Nilsson, Helen (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2016)
We are now more people on Earth than ever before and more people are living their lives in cities. In parallel, food production is getting more and more attention, not least due to climate change, and the expected climate change. Climate change which both change growing conditions and destroys growing conditions. Food production depends on farmland, but as the urban population grows, the cities surface grows as well. Not infrequently we find growing cities in areas with high-quality farmland. Thus growing cities often equal to farmland disappearing. If we look at the relationship between town and countryside, the growing city population also has moved further and further away from primary production of food. Thus it can be difficult to value both food production, farmland, and the importance of preserving production landscape. If we look at the city's planning, the ideal in recent has been the green-, the dense and the mixed city. However, the planning of the city's suburbs, the peri-urban landscapes, is often not planned after these ideals. The peri-urban landscapes often consists of external trade centers, or alternatively, left untouched without any real function while waiting for exploitation. At the same time, we see an increasing interest from urban residents to farm food, both for own use and to sale. But as a consumer, it can be difficult to get access to farmland, although there is unused, and unplanned urban land that could be used for large-scale city farming. The other side of the story is the countryside just outside the city boundary, the peri-urban landscape and the agriculture. As the city grows, it influences the large-scale farming, it becomes increasingly difficult to farm and the agriculture companies can be prevented in developing their businesses efficiently. Moreover, if the municipality owns of the farmland, they often leases at one year at time, which makes it even more difficult for the farmer.